Cannabinoids and agmatine as potential therapeutic alternatives for cisplatin-induced peripheral neuropathy - Donertas B; Cengelli Unel C; Erol K (Dove Medical Press, 2018)
Basak Donertas,* Cigdem Cengelli Unel,* Kevser Erol Department of Medical Pharmacology, Faculty of Medicine, Eskisehir Osmangazi University, Eskisehir, Turkey *These authors contributed equally to this work Abstract: Cisplatin is a widely used antineoplastic agent in the treatment of various cancers. Peripheral neuropathy is a well-known side effect of cisplatin and has the potential to result in limiting and/or reducing the dose, decreasing the quality of life. Unfortunately, the mechanism for cisplatin-induced neuropathy has not been completely elucidated. Currently, available treatments for neuropathic pain (NP) are mostly symptomatic, insufficient and are often linked with several detrimental side effects; thus, effective treatments are needed. Cannabinoids and agmatine are endogenous modulators that are implicated in painful states. This review explains the cisplatin-induced neuropathy and antinociceptive effects of cannabinoids and agmatine in animal models of NP and their putative therapeutic potential in cisplatin-induced neuropathy and antinociceptive effects of cannabinoids and agmatine in animal models of NP and their putative therapeutic potential in cisplatin-induced neuropathy.Keywords: agmatine, anandamide, cisplatin, neuropathy